MODELLING ISOTOPE FRACTIONATION DURING PRIMARY CRACKING OF NATURAL GAS: A REACTION KINETIC APPROACH - Cramer B.; Krooss B.M.; Littke R. (My University, 1998)
A numerical model has been developed to compute stable carbon isotope variations in natural gas (methane) by calculating 13CH4 and 12CH4 generation as a set of parallel first-order reactions of primary cracking. The goal of this work was to combine the description of isotope fractionation with established kinetic models for gas generation. Stable carbon isotope ratios of methane from sedimentary organic matter are characterized by the initial carbon isotope ratio of methane precursors within the organic matter and by a constant difference in activation energy between 12C- and 13C-methane generation from corresponding precursor sites. Methane generation is calculated separately for 12C- and 13C-methane. A difference in activation energy automatically implies a temperature dependence of fractionation processes which has not been taken into consideration in previous works. This new model offers a theoretical explanation and mathematical description of the observed variability of δ13C-values of methane during open-system pyrolysis experiments. Carbon isotopes of methane within natural gas of thermogenic origin can be simulated for any geological temperature history. The application of the method to two coaly rock samples of the Pokur formation from northern West Siberia results in simulated carbon isotope values of methane which are very similar to those in the natural gas within the reservoirs of the Pokur formation (δ13C1=−42‰ to −54‰). This finding supports a thermogenic origin of the gas at an early stage of maturation.